Technical assessment of Greenstone toward development of digital libraries in Iran. - Paknejad, Azad (Electronic Library, 2013)
Purpose – This paper tries to identify the extent of adoption and utility of Greenstone Digital Library Software (GDLS) in Persian language in Iran. What are the powerful capabilities and features of Greenstone and what about its programming bugs and errors toward information retrieval and storage in Persian language? Design/methodology/approach – The study adopted evaluative survey and direct observation through nine spectrums checklist based on Greenstone capabilities and features. Then viewpoints of computer and library and information science (LIS) specialists obtained and analyzed. After that, a digital Persian collection has been designed with Greenstone and analyzed. A statistical analysis scheme was employed to evaluate the software. Findings – The study obtained the following conclusions: there is similar consensus about GSLS effectiveness and capabilities between researcher and specialists. There is a lack of experts in Perl and Java programming language for upgrading of software in Iran. Further, software infrastructure especially in the interaction, support of standards and metadata features is powerful. Relatively poor user interface, incomplete sorting of Persian alphabet for "" characters, immature Unicode support like KWIC (or phind) index are some outstanding bugs. Research limitations/implications – The absence of complete and huge Persian digital library based on Greenstone was one of the major constraints of survey. Practical implications – If national entity supports localization of Greenstone, it will be a suitable solution for Persian digital library. Using Greenstone in the absence of financial resource for commercial software is a good choice. Originality/value – Using Greenstone to support digital libraries is a new trend as open source digital library solution in Iran for Persian language. This study can not only be a starting point for further discussions on the localization of open source digital library software, but also be applied to other researches.